Study on the anticorrosive behavior of new core-shell pigments for protection of reinforced concrete steel in sulfate environment. (15th August 2016) - Ahmed, N.M.; Mohamed, M.G.; Mabrouk, M.R.
Graphical abstract: Photos of uncoated and coated rebars in concrete samples after 28 days immersion in 5% MgSO4 . Highlights: New core-shell pigments based on silica fume covered with phosphates were prepared. Anticorrosive paints were applied on rebars for protection from sulfate attack. The rebar coatings did not affect the bond strength between rebar and concrete. Electrochemical tests showed good protection for paints with core-shell pigments. Paints containing silica fume showed less protection than core-shell pigments. Abstract: Sulfate exposure is considered high aggressive medium to reinforced concrete, therefore high efficient protection ways are needed to protect the steel rebars. In this work, new cheap eco-friendly anticorrosive pigments based on zinc, strontium, zinc.strontium phosphate/silica fume were prepared. These pigments contain thin shell of phosphates (10–20%) precipitated on silica fume waste (80–90%) using core-shell technique. These pigments were incorporated in anticorrosive paints to protect steel rebars from the sulfate ions effect in concrete. Tests were conducted to examine their corrosion protection efficiency and effect on the physical properties of concrete. Tests include (a) half-cell potential and electrochemical impedance spectroscopy to determine the corrosion protection of the coatings against corrosion and (b) bond strength between the coated rebar and concrete. The results showed that, the prepared core-shell pigments provided good corrosion protection to the rebars without affecting the bond between the rebar and concrete cover.